KONTRIBUSI IMAM AL-NAWAWI DALAM PENGEMBANGAN MADHHAB SHAFIâI - Aminuddin, Luthfi Hadi (IAIN Ponorogo, 2011)
In the history of Shafiiâs madhhab, the figure of Imam al-Nawa wi has a very significant role. The results of his Â ijtihadÂ is always used as a Shafi`iyah scholar reference, even when the scholars differed in opinions, then his idea regarded as